2011
DOI: 10.1007/s00247-011-1990-x
|View full text |Cite
|
Sign up to set email alerts
|

Interventional oncology: the future

Abstract: Interventional radiology techniques to treat oncological disease have already shown value in adults. The adoption and development of interventional oncology (IO) in children have been more limited and challenging. This relates to the approval process for new devices and agents, oncology group protocol limitations and the inherent hesitation of trying new treatments in children. This paper will discuss how new procedures are developed and approved, and the new therapies that will become available to better trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…52 Ethical assessment is made following general (assent and consent, benevolence, non-malevolence, justice and dignity) 22,43,50,54 or ad-hoc principles (feasibility, risk-minimisation, benefit maximisation, a risk-benefit profile comparable to alternatives, research interventions commensurate with patient's experience). 23,46,74 Despite efforts to follow these principles, two main limitations impinge the soundness and relevance of ethical assessments, namely their perceived exteriority ("I would really want to know who those people are"), 57 and their intrinsic variability, for they include comparisons ("alternatives") and valuations ("prospect of important direct benefit"). 8,23,46,54,69 Empirical data shall contribute to improve the consistency of ethical evaluations.…”
Section: Ethical Evaluation and State Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…52 Ethical assessment is made following general (assent and consent, benevolence, non-malevolence, justice and dignity) 22,43,50,54 or ad-hoc principles (feasibility, risk-minimisation, benefit maximisation, a risk-benefit profile comparable to alternatives, research interventions commensurate with patient's experience). 23,46,74 Despite efforts to follow these principles, two main limitations impinge the soundness and relevance of ethical assessments, namely their perceived exteriority ("I would really want to know who those people are"), 57 and their intrinsic variability, for they include comparisons ("alternatives") and valuations ("prospect of important direct benefit"). 8,23,46,54,69 Empirical data shall contribute to improve the consistency of ethical evaluations.…”
Section: Ethical Evaluation and State Interventionsmentioning
confidence: 99%
“…26,28,46,51,69,70,76 Other barriers relate to specifics of paediatric oncology (access to new compounds, small populations). 10,11,22,24,74,78 A policy shift is identified from conditionally allowing (as an exception), to positively encouraging, paediatric research. 28,68 This shift implies to reconcile the two legal logics of protection (safeguards, hard law) and of innovation (incentives, soft law).…”
Section: Ethical Evaluation and State Interventionsmentioning
confidence: 99%
“…As technology changes, it is imperative to appreciate the new direction of treatment so patients have access to well trained expert interventional radiologists and imaging experts working in proper environments with the right equipment [11]. Previous investigations have demonstrated that interventional radiology has value in adults [12]. This investigation provides evidence of the integration of navigation systems in the discipline and the benefits and potential drawbacks.…”
Section: Discussionmentioning
confidence: 84%
“…This evolution has been limited by the slow development and approval of new devices for use in children, patient size limitations, and the hesitation to test novel treatment approaches in pediatric patients. 28 There are numerous interventional radiology modalities available for the treatment of oncology patients, particularly those with liver tumors, with a range of experiences already published in the adult literature. 29 – 32 More recently, these interventional approaches have been introduced to the pediatric population as detailed in the following.…”
Section: Interventional Approachesmentioning
confidence: 99%